World Economic Outlook, October 2009 : Sustaining the Recovery. (World Economic Outlook; World Economic Outlook ;, 2009)
This edition of the World Economic Outlook explores the prospects for growth in the aftermath of the financial crisis. The fragile nature of the recovery will present many challenges. These include the need for continued strong monetary, fiscal, and financial policies, ongoing efforts to restore the financial sector to health, improvements in private demand, and preparation of exit strategies on the fiscal, monetary, and financial fronts. The first of two analytical chapters included in this edition, "Monetary Policy and Asset Prices: What Do We Learn from Booms and Busts?" explores whether there is a role for monetary policy in preventing asset price busts. The second, "Medium-Run Output Evolutions after Crises: A Historical Perspective," explores the effect of large economic shocks on output and its composition, including variations related to initial conditions, the type of shock, and economic policies.